Study of Microzoobenthos diversity in the Barambang River, Siantar Marihat District, Pematangsiantar City, Noth Sumatera Utara - Pakpahan, Dany Alberto; Barat, Welmar Olfan Basten; Saragih, Ewin Handoco (Sam Ratulangi University, 2024)
This study aims to; identify the diversity, uniformity, and dominance of Macrozoobenthos in the Bah Biak River area, Pematangsiantar City, North Sumatra Province. This study used a combination of two transect methods, namely line transects and quadrat transects. Determination of the research location using Purposive sampling techniques. Data analysis using qualitative and quantitative analysis. The results of the study showed that there were 3 species of Macrozoobenthos consisting of 2 classes with a total of 67,35% individuals. The diversity of Macrozoobenthos in the Bah Barambang River, Pematangsiantar City, North Sumatra Province is classified as moderate with a diversity index of H' = 0,71 – 0,73, the evenness index is classified as low ranging from 0,51 – 0,53 and the dominance index is classified as low. Keywords: Macrozoobenthos, River, Diversity Abstrak Penelitian ini bertujuan untuk; Untuk mengidentifikasi keanekaragaman, keseragaman dan dominansi Makrozoobenthos pada kawasan Sungai Barambang Kota Pematangsiantar Provinsi Sumatera Utara. Penelitian ini menggunakan kombinasi dua metode transek yaitu transek garis dan transek kuadrat. Penentuan lokasi penelitian menggunakan teknik purposive sampling. Analisis data menggunakan analisis kualitatif dan kuantitatif. Hasil penelitian diketahui bahwa terdapat 3 spesies Makrozoobenthos yang terdiri dari 2 kelas dengan jumlah keseluruhan 67,35% individu. Keanekaragaman Makrozoobenthos di Sungai Bah Barambang Kota Pematangsiantar Provinsi Sumatera Utara tergolong sedang dengan indeks keanekaragaman H' = 0,71 – 0,73, indeks keseragaman rendah berkisar antara 0,51 – 0,53 dan indeks dominansi rendah. Kata Kunci: Makrozoobentos, Sungai, Keanekaragaman.